Measurement of the jet mass in highly boosted t(t)over-bar events from pp collisions at root s=8TeV - Sirunyan, A. M. (2017)
The first measurement of the jet mass m(jet) of top quark jets produced in t (t) over bar events from pp collisions at root s = 8 TeV is reported for the jet with the largest transverse momentum p(T) in highly boosted hadronic top quark decays. The data sample, collected with the CMS detector, corresponds to an integrated luminosity of 19.7 fb(-1). The measurement is performed in the lepton+jets channel in which the products of the semileptonic decay t -> bW with W -> l nu where l is an electron or muon, are used to select t (t) over bar events with large Lorentz boosts. The products of the fully hadronic decay t -> bW with W -> q (q) over bar ' are reconstructed using a single Cambridge-Aachen jet with distance parameter R = 1.2, and pT > 400 GeV. The t (t) over bar cross section as a function of m(jet) is unfolded at the particle level and is used to test the modelling of highly boosted top quark production. The peak position of the m(jet) distribution is sensitive to the top quark mass m(t), and the data are used to extract a value of m(t) to assess this sensitivity.